If it's not what You are looking for type in the equation solver your own equation and let us solve it.
18q-4(3+q)=146
We move all terms to the left:
18q-4(3+q)-(146)=0
We add all the numbers together, and all the variables
18q-4(q+3)-146=0
We multiply parentheses
18q-4q-12-146=0
We add all the numbers together, and all the variables
14q-158=0
We move all terms containing q to the left, all other terms to the right
14q=158
q=158/14
q=11+2/7
| 5u-9=9-u | | a-8/12=2a=5/3 | | 11-4x=45 | | 3(2x+4)-6=2(2x-8)+5 | | 5/n-2=-1/n | | 12x+4=-8x-56 | | -1+a/6=0 | | 6p-4=4p-1 | | -1+a/6=6 | | -3/4=-9p/5 | | Y=1.3x-2.7 | | 6x7x=27 | | 10=-4m-m-2 | | 7m=4m+6 | | -9=-15+v/3 | | 3.5/18=z/26 | | 8+6y=-1+6y | | 9m-280=7m+120 | | 2d+1.6=6(1.3+1) | | 15-3t-4t=22 | | -3=7+a | | 2-6x=2x+2 | | 2y-3(2+y)=33 | | 3+7x=-67 | | -5(-2)=20-5c+10 | | (5y+4)(y+4)=-3(5y+4) | | 5/6p=2/9 | | -20+x/15=-17 | | 1-8/9x=5/6 | | a–7=8–(9+a) | | -2p+8=5-(6p+2) | | 33-4x=11x-4x |